What Determines The Optimal Cadence? (1996)
As the sport of cycling has evolved, training methods have changed, equipment has been refined, and performances have been enhanced. However, one aspect of cycling performance has remained relatively unchanged, that is, the freely chosen cadences of cyclists during training and racing. Few coaches or exercise scientists would argue that cadences of 90 + 5 rpm are typical of those used during world-class performances in road racing or time-trialing, particularly over level terrain. Furthermore, there are no compelling reasons, either scientific or popular, that would lead a coach to recommend a significantly lower or higher cadence to an elite performer. Therefore, the working hypothesis of this article is that cadences in the range 85 to 95 rpm are optimal for performance. From a scientific point of view the obvious question of significance is then, "Why are cadences of 85 to 95 rpm, so typical of elite performers during competition, optimal?" The purpose of this article is to review and examine the multidisciplinary exercise science literature concerning optimal cadence, present one possible interdisciplinary explanation for the optimal cadence phenomenon, and address some common generalizations about cyclists and noncyclists that appear to be incorrect. Taken from : Cycling Science - Summer 1996 - What Determines The Optimal Cadence?